Autoagregação da 5,10,15,20-tetrakis(4-metoxifenil)porfirina (tmpp): estudos espectroscópicos e análises multivariadas - Braga,Gustavo (2014)
In this work, the spectroscopic properties of 5,10,15,20-tetrakis(4-methoxyphenyl)porphyrin (TMPP) in solvents of different polarities and water/ethanol mixtures were studied by electronic absorption spectroscopy and resonance light scattering associated with statistical analysis. The molar absorption coefficient and emission maximum of TMPP were dependent on solvent polarity. In the water/ethanol mixture, TMPP remained monomeric up to 25% of water, when it reaches its critical aggregation percentage. Oblique head-to-tail aggregate was found at intermediate water content (35 - 55%), while formation of a J-type aggregate was observed at higher water content (> 60%).